ACADEMIC, FINANCIAL, AND OTHER FACTORS AFFECTING PERFORMANCE IN THE AGRICULTURAL AND BIOSYSTEMS ENGINEERING BOARD EXAMINATION (2018, 2019, AND 2021) OF BULACAN AGRICULTURAL STATE COLLEGE - Meriam F. Sulit; Isabel Samantha C. Belonio; Daniel Alexis H. Belonio; Joselito D. Tucit; Cresan Joy V. Villaroman (International Conference on Multidisciplinary Research Perspective, 2025)
State Colleges and Universities (SCUs) in the Philippines, licensure examination performance is a legally mandated, fundamental measure of institutional success and program effectiveness. This critical metric is strictly enforced by regulatory bodies, such as the Commission on Higher Education (CHED), as a key requirement for both program accreditation and official compliance standards. Therefore, investigating the key factors affecting board exam performance is essential for effectively understanding, measuring, and implementing targeted interventions to sustain or improve the institution’s status. Analysis of Bulacan Agricultural State College – Agricultural and Biosystems Engineering (BASC - ABE) Program takers (2018, 2019, 2021) showed a first-attempt passing rate of 67.70%. The correlation results provide clear strategic direction for improving this performance: academic performance is key, as taker’s GWA showed a moderate correlation with passing, establishing achievement during college as a reliable predictor of board exam success; however, working status presents a barrier, showing a negative moderate correlation that indicates the demands of employment significantly interfere with study time and readiness. Furthermore, enrolment in a review center had only a very low correlation, suggesting that the quality and personalized effort in preparation matter significantly more than the simple act of enrolment. Finally, taking the examination during the pandemic showed a high correlation, highlighting the overwhelming influence of external factors on cohort performance. In terms of challenges, respondents overwhelmingly reported emotional distress, including nervousness, pressure, and mental blockage. To address this, the respondents strongly recommend the institution conduct refresher programs or mock examinations and, critically, prepare graduates not just theoretically but also mentally and emotionally for the licensure examination. Further suggestions include implementing more hands-on, output-based learning in the curriculum and upgrading laboratory equipment to create a more conducive learning environment.